2020
DOI: 10.3390/brainsci10110797
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Behavioral, Physiological, and Neurobiological Cognitive Regulation Alterations in Obsessive-Compulsive Disorder

Abstract: Obsessive-compulsive disorder (OCD) is characterized by cognitive regulation deficits. However, the current literature has focused on executive functioning and emotional response impairments in this disorder. Herein, we conducted a systematic review of studies assessing the behavioral, physiological, and neurobiological alterations in cognitive regulation in obsessive-compulsive patients using the PubMed database. Most of the studies included explored behavioral (distress, arousal, and frequency of intrusive t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 67 publications
4
6
0
Order By: Relevance
“…Research on problem-solving strategies in OCD is scarce, however, one study revealed no impaired problem-solving strategies in adults with OCD, measured using performance-based EF tasks [ 36 ]. Regarding emotion regulation, our findings are in line with evidence indicating that difficulties with emotion regulation is related to several psychiatric disorders in adults, including OCD, where it is often characterized by diminished reappraisal abilities and increased use of suppression strategies [ 37 ]. Our results expand this body of research by showing that overall EF deficits are not specific for OCD but extend to pediatric anxiety disorders.…”
Section: Discussionsupporting
confidence: 88%
“…Research on problem-solving strategies in OCD is scarce, however, one study revealed no impaired problem-solving strategies in adults with OCD, measured using performance-based EF tasks [ 36 ]. Regarding emotion regulation, our findings are in line with evidence indicating that difficulties with emotion regulation is related to several psychiatric disorders in adults, including OCD, where it is often characterized by diminished reappraisal abilities and increased use of suppression strategies [ 37 ]. Our results expand this body of research by showing that overall EF deficits are not specific for OCD but extend to pediatric anxiety disorders.…”
Section: Discussionsupporting
confidence: 88%
“…Passive and repetitive focus on the problem (also referred to as rumination) worsens the emotional distress and may lead to depression (Hatzenbuehler et al, 2009 ; Miranda et al, 2013 ; Burton et al, 2018 ); therefore, rumination is a maladaptive strategy for dealing with psychological stress. Likewise, thought suppression (redirection of attention to other content) is considered maladaptive as it may impair memory (Richards, 2004 ) or lead to obsessive compulsive disorder (Ferreira et al, 2020 ). Concealment of a stigmatizing condition, albeit not immediately related to emotional regulation, is another non-productive strategy since it is associated with greater psychological distress (Quinn et al, 2014 ).…”
Section: About Stigma Stigmatizing Attitudes and Stigmatizationmentioning
confidence: 99%
“…OCD is characterized by recurrent obsessive thoughts and intrusions (obsessions) and habitual behaviours (compulsions). These symptoms disturb patients' daily activity and affect their quality of life (Drubach, 2015;Ferreira et al, 2020). Around 1-3% of children experience OCD symptoms and unlike adult OCD, boys are more commonly affected by the symptoms than girls.…”
Section: Introductionmentioning
confidence: 99%